Design and fabricate of solar cooker / Muhamad Syamirul Abu Shah - Abu Shah, Muhamad Syamirul (2022)
This project about design and fabricate a solar cooker. Using heat transfer science concept than focus on heat conduction, conservation radiation and insulation. The idea of design was trigger by privies design by another creator. overall dimension of product 1m x 1m x 0.7m. The project is generated for helping people in reduce their daily life cost by deal with almost zero cost on prepare food for family. They do not need to provide additional money on buying gas/fuel or paid electric bill on gas or electrical stove. good design was generated by Consider all factor like effeteness and factor for good performant.